2016
DOI: 10.1103/physrevc.94.054617
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear fragmentation and charge-exchange reactions induced by pions in the Δ-resonance region

Abstract: Dynamics of the nuclear fragmentations and the charge exchange reactions in pion-nucleus collisions near the ∆(1232) resonance energies has been investigated within the Lanzhou quantum molecular dynamics (LQMD) transport model. An isospin, momentum and density-dependent pionnucleon potential is implemented in the model, which influences the pion dynamics, in particular the kinetic energy spectra, but weakly impacts the fragmentation mechanism. The absorption process in pion-nucleon collisions to form the ∆(123… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition, the behavior of the pion energy spectral or pion flow could also be sensitive to the pion potential [26][27][28][29][30]. The reason is that, for beam energy below 0.3…”
Section: Introduction πmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the behavior of the pion energy spectral or pion flow could also be sensitive to the pion potential [26][27][28][29][30]. The reason is that, for beam energy below 0.3…”
Section: Introduction πmentioning
confidence: 99%
“…Consequently, one can expect that the in-medium effects on pion propagation and collision gradually become more important, and the on-shell transport seems reasonably accurate. The relativistic Vlasov-Uehling-Uhlenbeck (RVUU) model calculations showed that the ratio is reduced by approximately 10% by considering the in-medium pion dispersion relation, and a large effect is also observed in isospin-dependent Boltzmann-Uehling-Uhlenbeck (IBUU) [28] calculations at subthreshold energy. There exists model dependence on the in-medium effects on the pion production mechanism in the transport model simulations partly due to the separate treatments on pion potential, the cross sections, and decay widths.…”
Section: Introduction πmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental information about the mass, width, and decay modes of baryonic resonances in free space and in nuclear environments is crucial for validating theoretical models describing the internal structure of the nucleon and its excited states. Moreover, the investigations of baryon resonances in nuclear matter are a natural extension of nuclear physics at the intersection of nucleonic and subnuclear degrees of freedom, elucidating open problems such as the role of resonances in three-body interactions [2,3] and neutron star matter [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering experiments showing for the first time the in-medium excitation of the resonance in peripheral single isobaric charge-exchange reactions were performed in the 1980s at the Laboratoire National SATURNE in Saclay (France). In these experiments, the ejectiles produced in collisions of stable relativistic projectiles of 3 He, 12 C, 20 Ne, and 40 Ar on different target materials were identified and momentum analyzed with the magnetic spectrometer SPES-IV [22][23][24][25]. The high-resolving power of the spectrometer made it possible to prove the excitation of the resonance from the velocity recoil experienced by the ejectiles due to the pion emission.…”
Section: Introductionmentioning
confidence: 99%